Resistance to the crayfish plague pathogen, Aphanomyces astaci, in two freshwater shrimps - Svoboda, J; Mrugała, A; Kozubíková-Balcarová, E; Kouba, A; Diéguez-Uribeondo, J; Petrusek, A (Journal of invertebrate pathology, 2014)
Aphanomyces astaci, the causal agent of the crayfish plague, has recently been confirmed to infect also freshwater-inhabiting crabs. We experimentally tested the resistance of freshwater shrimps, another important decapod group inhabiting freshwaters, to this pathogen. We exposed individuals of two Asian shrimp species, Macrobrachium dayanum and Neocaridina davidi, to zoospores of the pathogen strain isolated from Procambarus clarkii, a known A. astaci carrier likely to get into contact with shrimps. The shrimps were kept in separate vessels up to seven weeks; exuviae and randomly chosen individuals were sampled throughout the experiment. Shrimp bodies and exuviae were tested for A. astaci presence by a species-specific quantitative PCR. The results were compared with amounts of A. astaci DNA in an inert substrate to distinguish potential pathogen growth in live specimens from persisting spores or environmental DNA attached to their surface. In contrast to susceptible crayfish Astacus astacus, we did not observe mortality of shrimps. The amount of detected pathogen DNA was decreasing steadily in the inert substrate, but it was still detectable several weeks after zoospore addition, which should be considered in studies relying on molecular detection of A. astaci. Probably due to moulting, the amount of A. astaci DNA was decreasing in N. davidi even faster than in the inert substrate. In contrast, high pathogen DNA levels were detected in some non-moulting individuals of M. dayanum, suggesting that A. astaci growth may be possible in tissues of this species. Further experiments are needed to test for the potential of long-term A. astaci persistence in freshwater shrimp populations.
Keywords: interakce hostitele a patogenu; Palaemonidae; Host range; Freshwater shrimp; Host-Pathogen Interactions; Decapoda; Aphanomyces; Crayfish plague; Animals; Aphanomyces astaci; zvířata; Disease Resistance; Pathogen transmission; odolnost vůči nemocem; Decapoda (Crustacea)